The Impact of Funding Liquidity on European Bank Risk-Taking Behaviour - Yasir Maulana; Nugraha Nugraha; Maya Sari; In Min (Jurnal Akuntansi dan Pajak, 2022)
Funding liquidity as the bank ability to generate funds by disbursing assets to meet short-term financial liabilities is very important because of bank intermediary activities. This study conduct to measure the effect of funding liquidity on bank risk-taking behaviour. We used the panel data regression method for data processing with Pooled Least Square (PLS), Fixed Effect Model (FEM), and Random Effect Model (REM). As this study uses bank data from different countries as well as banking and regulatory conditions that different over time, it is predicted that regression parameters are not constant between time and sample. The data period of public-listed commercial bank in Europe are from 2004 to 2016. The result of this study shows that the problem of low profitability in European banks may trigger banks to take bigger risks to achieve higher profits. These results indicate that European banks with higher levels of funding liquidity tend to have more aggressive risk-taking behavior in the future. Bank risk-taking behavior in response to increased liquidity was generally lower during the global financial crisis period. This could be due to increased risk aversion and a tighter monitoring process during this period.